Studi Pengelolaan Limbah Aki Kering Dan Aki Basah (Studi Kasus di Indramayu) - Indah Dhamayanthie; Dian Farkhatus Sholikha; Anisa Rizka Nurjanah (Jurnal Migasian, 2023)
Abstract. Accumulator or battery is a device that can store energy (generally electrical energy) in the form of chemical energy. The batteries that are widely used by the community are dry batteries and wet batteries. Use it continuously will be aware of events anywhere. In Indramayu there is still a lot of used battery waste that is not treated properly and properly. This can cause pollution to the environment, so there is a need for management of used battery waste. The purpose of this final project is to determine the percentage of use of dry and wet batteries in motorized vehicles, the performance of dry and wet batteries in motorized vehicles, the waste generated by dry and wet batteries, waste management of dry and wet batteries in motor vehicles and to find out type of battery that is friendly to the environment. The implementation of the final task is carried out by collecting literature, surveys and interviews. From the results of the survey, it was stated that 75% of students and the academic community of Akamigas Balongan used dry batteries and 25% used wet batteries. The performance of dry and wet batteries is the same using the principle of emptying and charging. As for the most waste generated from dry batteries. Waste generated by dry and wet batteries, namely liquid and solid waste comes from used battery containers and lead/liquid, where each waste has its own management. From this study, the type of battery that is environmentally friendly is dry battery with a survey percentage of 80%. Keywords: accumulator, wet accu, dry accu, environmentally friendly accu, waste